Bearing capacity of driven pile and determination of inhomogeneous mudstone around the pile - Zhang, Yamei; Sun, Gan; Bai, Xiaoyu; Sang, Songkui; Han, Jianyong; Yan, Nan; Zhang, Mingyi; Gao, Xiaodong; Li, Weiqi (Frontiers in Earth Science, 2023)
Whether the inhomogeneity of mudstone foundation leads to abnormal bearing capacity of the driven pile remains controversial. This study introduces the standard penetration test hammering number and needle penetration strength for quantitative analysis by macroscopic observation of the engineering field on the mudstone stratum self-structure and microscopic observation by simple and feasible electronic magnification. The analysis of typical engineering examples demonstrated that the abnormal bearing capacity of piles in the mudstone stratum was related to mudstone inhomogeneity. This study also proposes a method of evaluating mudstone uniformity using the heterogeneous index η, in which η > 2 suggests the need for engineering measures. These findings assist in determining a reasonable solution to the problem of abnormal bearing capacity at driven piles in mudstone foundations.